Evaluation the performance of co-encapsulated beads formed with a probiotic culture and L-ascorbic acid against pathogens and simulated gastric conditions - and Subrota Hati, Koushik Das, Kunal M Gawai, Mitesh Hingu, Ashish Shendurse (Indian Journal of Dairy Science, 2025)
The present investigation was conducted on beads formed from extrusion and emulsion methods having a co-encapsulated probiotic culture and L-ascorbic. These were tested against pathogens and simulated gastric conditions. gastric juice tolerance of encapsulated probiotic culture has been shown. Comparing treatment means, there was a significant difference (p